The Accumulation of Phenolic Compounds in Genetically Selected Amaranthus hybridus is Influenced by Endophytic Natural Growth Regulator - Wudeneh Letchamo; Thomas Hartman; André Gosslin; Nazim A. Mamedov; Lyle Craker (International Journal of Secondary Metabolite)
Amaranth (Amaranthus spp. L.) (Amaranthaceae), an endemic plant in Central and South America, grows worldwide, being cultivated in many temperate and tropical countries. Although several species of amaranth are frequently considered weeds, the plant is recognized as a food, constructive medicine, a source of protein and minerals livestock feed. The plant is widely cultivated, promoted, and increasingly consumed as a leafy vegetable and traditional medicine in Africa. Despite progressive genetic improvement and modern plant growing technologies, unfavorable climatic and ecological factors reduce the yield, and quality of the active plant botanicals. The role of bio-transformed endophytic microbial plant growth regulator formulation (BESF) on yield and accumulation of phenolic compounds in amaranth leaves is poorly understood. The current study assessed the effects of pre-sowing seed treatments with 0.0 %, 0.2 % and 0.4 % concentrations of BESF solution on germination, leaf yield, flavor and phenolic content in genetically selected Amaranthus hybridus var. cruentus. Data collected were subjected to analysis of variance (ANOVA). Significant treatment means were separated using Tukey test at p<0.05. BESF significantly increased fresh marketable leaf yield by over 360 kg/ha (29